Persisting symptoms in patients with Hashimoto’s disease despite normal thyroid hormone levels: Does thyroid autoimmunity play a role? A systematic review - Groenewegen, Karelina L.; Mooij, Christiaan F.; van Trotsenburg, A.S. Paul (Journal of translational autoimmunity (Online), 2021)
Patients with hypothyroidism due to Hashimoto’s disease (HD) may experience persisting symptoms despite normal serum thyroid hormone (TH) levels. Several hypotheses have been postulated to explain these persisting symptoms. We hypothesized that thyroid autoimmunity may play a role. A systematic literature review. A PubMed search was performed to find studies investigating the relation between the presence of thyroid autoimmunity and (persisting) symptoms. Included studies were critically appraised by the Newcastle – Ottawa Scale (NOS) and then subdivided into (A) disease-based studies, comparing biochemically euthyroid patients with HD, and euthyroid patients with non-autoimmune hypothyroidism or euthyroid benign goitre, and (B) (general) population-based studies. Due to different outcome measures among all studies, meta-analysis of data could not be performed. Thirty out of 1259 articles found in the PubMed search were included in this systematic review. Five out of seven disease-based studies found an association between thyroid autoimmunity and symptoms or lower quality of life (QoL). Sixteen of 23 population-based studies found a comparable positive association. In total, the majority of included studies reported an association between thyroid autoimmunity and persisting symptoms or lower QoL in biochemically euthyroid patients. (Thyroid) autoimmunity seems to be associated with persisting symptoms or lower QoL in biochemically euthyroid HD patients. As outcome measures differed among the included studies, we propose the use of similar outcome measures in future studies. To prove causality, a necessary next step is to design and conduct intervention studies, for example immunomodulation vs. placebo preferably in the form of a randomized controlled trial, with symptoms and QoL as main outcomes. •This review reports on a relation between thyroid autoimmunity and symptoms.•Persisting symptoms in euthyroid HD patients may be associated with autoimmunity.•Thyroid autoimmunity and symptoms were associated in population-based studies.